Acrossocheilus longipinnis (Wu 1939), a senior synonym of Acrossocheilus stenotaeniatus Chu & Cui 1989 from the Pearl River basin (Teleostei: Cyprinidae) - Yuan, Le-Yang; Chan, Bosco Pui Lok; Zhang, E (Zootaxa, 2012)
A detailed morphological comparison of the currently recognized subspecies, Acrossocheilus iridescens longipinnis andA. i. iridescens, shows that there are differences in body coloration of juveniles and some osteological characters, inaddition to the structure of the first branched dorsal-fin ray and the shape of the distal edge of the dorsal fin which arecurrently used to distinguish them. These differences support the taxonomic elevation of the two subspecies to species.Based on examination of the type specimens of Acrossocheilus stenotaeniatus, and comparison with A. longipinnis, it isconcluded that A. longipinnis is a senior synonym of A. stenotaeniatus. Acrossocheilus longipinnis is redescribed. Thecurrent generic classification of the two species is discussed based on the body coloration of juveniles and ontogenetic color change.